PENINGKATAN KOMPETENSI GURU MELALUI PELATIHAN DIGITALISASI PENDIDIKAN PADA GURU MADRASAH DI KP. LEGOK PADA MASA PANDEMI COVID-19 - Agustien Dwi Hayanty; Herul Anwar; Halvi Julmi’raj (Institut Madani Nusantara, 2022)
With the COVID-19 pandemic, all aspects of life experience the same problems, be it social, economic, or educational aspects. In the aspect of education itself, it has resulted in schools changing their learning patterns significantly, which was initially done face-to-face but had to switch to a network. Community empowerment through digitalization training for Madrasah Diniyah teachers in Kp. Legok Desa Mekarsari is an important step to take, because it aims to improve the competence of madrasa teachers so that they can be applied in teaching and learning activities. The empowerment method used in this service program is to use the PAR (Participation Action Research) method. The scope of this activity is the teachers in Madrasah Diniyah. We involved ourselves directly in the field as teachers of this training, and the results of this training activity received a good response from the teachers. This training program is an option for the community, especially teachers in terms of self-development to improve their competencies, so that they strive to create quality, skilled, and innovative human resources, especially during the current covid-19 pandemi.